2003
DOI: 10.1080/03075070309292
|View full text |Cite
|
Sign up to set email alerts
|

From First to Second Generation Professional Doctorate

Abstract: The development of Professional Doctorates in Australia and elsewhere in the 1990s has lead to a reconsideration of the nature of the doctoral award. There is evidence in Australia for the emergence of what has been called a second generation of Professional Doctorates. In this paper the features of the latter are analysed using three case studies. Research into an EdD and its subsequent development from a first to second generation program are also presented. The key conceptualisation used for the analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
15

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 6 publications
0
63
0
15
Order By: Relevance
“…Maxwell (2003) traces the evolution from first to second generation professional doctorate, and Bourner, Bowden and Laing (2001) identified 20 distinctive features common to professional doctorates in English universities. Pearson (1996) sees the professional doctorate ''as a form of professional education in which students are introduced to the professional practice of research and scholarship, with the supervisor responsible for assisting students to become independent practitioners''.…”
Section: Diversity Of Provision -Emergence Of New Forms Of Doctoratementioning
confidence: 99%
“…Maxwell (2003) traces the evolution from first to second generation professional doctorate, and Bourner, Bowden and Laing (2001) identified 20 distinctive features common to professional doctorates in English universities. Pearson (1996) sees the professional doctorate ''as a form of professional education in which students are introduced to the professional practice of research and scholarship, with the supervisor responsible for assisting students to become independent practitioners''.…”
Section: Diversity Of Provision -Emergence Of New Forms Of Doctoratementioning
confidence: 99%
“…Maxwell (2003) demonstrated how PDs have developed to become more involved with professional knowledge. Bourner et al (2001), in a survey of English universities identified twenty distinctive features of PDs and called for more research on these distinguishing features.…”
Section: An Expanding Literature Regulation and Guidancementioning
confidence: 99%
“…In categorising the development of PDs, discipline-specific PDs such as the EdD and DBA have been identified by Maxwell (2003) as 'second-generation' and have moved away from some of the assumptions about academic research traditionally associated with the PhD. Maxwell (2003) demonstrated how PDs have developed to become more involved with professional knowledge.…”
Section: An Expanding Literature Regulation and Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…Apparently consistent with Berkeley, or perhaps vice versa, Maxwell 4 noted that professional doctorates in Western Europe are such that "scientists not only acquire specialised knowledge through their research but apply that knowledge in political, economic, social and cultural contexts" (p.279).…”
Section: Characteristics Of Existing Professional Doctorate Programsmentioning
confidence: 98%